Association between vaginal washing and group B Streptococcus colonization from periconception through the first trimester of pregnancy in a cohort of Kenyan women - Clayton S. Jisuvei; John Kinuthia; Barbra A. Richardson; Sujatha Srinivasan; Erica M. Lokken; Kishor Mandaliya; Walter Jaoko; Matthew Munch; Tina L. Fiedler; David N. Fredricks; Raymond Scott McClelland (PLoS ONE, 2026)
Introduction Vaginal washing has been associated with adverse reproductive health outcomes including pelvic inflammatory disease, reduced fecundability, and HIV acquisition. This analysis tested the hypothesis that vaginal washing is associated with increased risk of group B streptococcus (GBS) colonization. Method Women planning pregnancies contributed monthly visits during which vaginal fluid specimens were collected and urine pregnancy testing was performed. In women who became pregnant, additional samples were collected at 9–12 weeks gestation. Broad-range 16S rRNA gene PCR with next generation sequencing (NGS) was performed to identify vaginal bacterial species. Generalized estimating equations with a log link, Poisson family, independent correlation structure and robust errors were used to generate prevalence ratios comparing the prevalence of GBS detection at vaginal washing visits versus non-vaginal washing visits. Results The 189 women who became pregnant contributed 506 samples used in this analysis. Samples were collected at periconception 196 (38.9%), early first trimester 151 (29.8%), and late first trimester visits 159 (31.4%). The prevalence of GBS during the three time periods was 20/196 (10.2%), 11/151 (7.3%) and 2/159 (1.3%) respectively. Vaginal washing was practiced by 51/196 (26.0%), 27/151 (17.9%) and 32/159 (20.1%) participants during the three time periods. Compared to visits with no vaginal washing, there was no increased prevalence of GBS detection at visits where vaginal washing with water was reported (prevalence ratio [PR] 0.51, 95% confidence interval [CI] 0.16–1.62). However, the prevalence of GBS detection was nearly five-fold higher at visits when vaginal washing using water and soap was reported (PR 4.66, 95% CI 1.51, 14.33). Conclusion Vaginal washing with soap and water was associated with a nearly five-fold increase in GBS prevalence. Future studies should evaluate this association in later pregnancy and peripartum. Cessation or modification of vaginal washing practices could be a useful strategy for decreasing GBS colonization.